Fenomena Masuknya Tokoh Agama Dan Pesantren Dalam Politik Praktis Serta Dampak Terhadap Pandangan Masyarakat - Junaedi, Erik; Kiram, Syaiful; Fahkrurrazi; Junaidi, Erik (Universitas Islam Negeri Raden Intan Lampung, 2025)
The 2024 General Election shows the politicization of religious roles and the fragmentation of spiritual authority in large religious organizations such as Nahdlatul Ulama. This study aims to analyze the pattern of public perception of the involvement of religious figures in practical politics in the 2024 General Election and examine its impact on religious legitimacy and social cohesion in Indonesia. The research method uses a qualitative descriptive approach through library research with qualitative content analysis and thematic analysis of 127 selected sources covering laws and regulations, indexed academic publications (2014-2024), and official documentation of religious organizations. That the involvement of religious figures in practical politics is driven by multidimensional motivations that include normative aspects (application of Islamic values ​​in public policy), instrumental (access to political resources), and expressive (expression of religious identity in the public sphere). The political strategies implemented show the adaptation of religious traditions to modern political technology through lectures, political party coalitions, and the use of social media. The impact of involvement is ambivalent: positive in increasing political participation and strengthening moral values ​​in politics, but negative in creating the politicization of religion and social fragmentation. Variations in involvement patterns show different regional characteristics, ranging from accommodative patterns in East Java, integrative in West Java, to patron-client systems in Madura.